The role of the investigation agencies in maintaining a fair trial - Bouaoune, Nidhal (Journal of Human Sciences, 2021)
The investigation stage is an essential stage in the public case, as it contributes to determining the identity of the criminal and the character of the crime and presenting them in their true form to the court in order to ensure that the procedures and the measures related to them are carried out in a sound manner without any defect or suspicion, and this is to ensure the principle of the trial It is fair that every person is considered innocent until a regular judicial authority proves his guilt in the context of a fair trial that provides him with the necessary guarantees to defend him in relation to all the parties that have been in that. The last is Her sovereign and authority over it.